2015
DOI: 10.2175/106143015x14212658614793
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Metal and Sulphate Loads in Acid Mine Drainage Receiving Water Dams – Variables Regionalization by Cluster Analysis

Abstract: The Sancho Reservoir (Iberian Pyrite Belt, SW Spain) is nourished by the waters of the river Meca, which is affected by acid mine drainage (AMD) processes from the abandoned Tharsis mine. The aim of the present work is to study the hydrochemical variations in this reservoir, in order to define potential stratification processes in metal load and sulphates. A stratified sampling from the surface, with one meter deep intervals to the bottom of the dam, was performed. The results show a clear stratification of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…These two biological variables were used as a summary in the total matrix of 118 diatom species. Cluster analysis has been widely used for the geochemical characterization of AMD media [11,42,43]. Cluster analysis is used to define a series of techniques, basically algorithms, whose objective is to find similar groups of items or variables (sampling points) that are grouped together in clusters.…”
Section: Methodsmentioning
confidence: 99%
“…These two biological variables were used as a summary in the total matrix of 118 diatom species. Cluster analysis has been widely used for the geochemical characterization of AMD media [11,42,43]. Cluster analysis is used to define a series of techniques, basically algorithms, whose objective is to find similar groups of items or variables (sampling points) that are grouped together in clusters.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that, according to Mondal et al, (2015), the stratification of the water column due to temperature variation is a seasonal phenomenon in lakes and reservoirs. The study by Grande et al, (2015), on stratification of Metallic and Sulfate Loads, carried out in Dams in the Iberian Pyritic Belt in southwestern Spain, showed that Fe and Mn concentrations increase in the deeper reservoir layer.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…The annual average rainfall value in the basin is 812 mm, 50% of which occurs betwe October and February (wet season) [38]. Although classical statistics is a useful methodology for modeling this type of system [22,27,28] by using tools such as Cluster Analysis, Factorial Analysis and Principal Component Analysis, Fuzzy Logic goes one step forward, allowing more information to be extracted from the same database. The reason for this is that classical statistics works by means of a binary system of "ON-OFF", "YES-NO" or "White-Black".…”
Section: Introductionmentioning
confidence: 99%